A novel eight-way power combiner on suspended substrate stripline for Ku-band applications - Pham Thanh Cong; Vu Le Ha; Luong Duy Manh (Journal of Military Science and Technology, 2024)
This work proposes a novel 8-way power combiner implemented using suspended substrate stripline technology for Ku-band applications. The equivalent circuit of the design is analyzed to obtain parameters for the physical realization of the structure. The combiner is well matched at both input and output ports with VSWR better than 1.6:1, achieves low insertion loss of less than 1dB and isolation of more than 16.8 dB over the range from 12 GHz to 18 GHz. The structure is also able to handle high thermal dissipated power due to its housing, hence, suitable to find application in high power-amplifier subsystems.